2018
DOI: 10.3892/ijo.2018.4426
|View full text |Cite
|
Sign up to set email alerts
|

NRG1 regulates redox homeostasis via NRF2 in papillary thyroid cancer

Abstract: Thyroid cancer is a common endocrine cancer, of which papillary thyroid cancer (PTC) is the most common type. Neuregulin 1 (NRG1), a glycoprotein mediating cell-cell signaling, plays vital roles in cellular activities; however, its role in PTC progression remains poorly understood. In this study, we performed immunohistochemistry in 196 samples from patients and found that NRG1, a potential prognostic marker is highly expressed in PTC compared with adjacent normal tissues. Cell Counting kit-8 (CCK-8) and clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Among PTC samples with strong expression of Nrf2, the BRAF V600E mutation was not more frequent compared to a general PTC cohort, suggesting that Nrf2 activation is not exclusively associated with BRAF mutation (42). Another study focused on neuregulin 1 (NRG1), a member of the epidermal growth factor-like family, which was found to be overexpressed in PTC (58, 59). NRG1 positively impacts Nrf2 protein levels in PTC and stimulates the upregulation of its target genes, including NQO1, GCLC , and GCLM (glutamate cysteine ligase, modulatory subunit) (58).…”
Section: Thyroid Carcinomasmentioning
confidence: 99%
See 2 more Smart Citations
“…Among PTC samples with strong expression of Nrf2, the BRAF V600E mutation was not more frequent compared to a general PTC cohort, suggesting that Nrf2 activation is not exclusively associated with BRAF mutation (42). Another study focused on neuregulin 1 (NRG1), a member of the epidermal growth factor-like family, which was found to be overexpressed in PTC (58, 59). NRG1 positively impacts Nrf2 protein levels in PTC and stimulates the upregulation of its target genes, including NQO1, GCLC , and GCLM (glutamate cysteine ligase, modulatory subunit) (58).…”
Section: Thyroid Carcinomasmentioning
confidence: 99%
“…Another study focused on neuregulin 1 (NRG1), a member of the epidermal growth factor-like family, which was found to be overexpressed in PTC (58, 59). NRG1 positively impacts Nrf2 protein levels in PTC and stimulates the upregulation of its target genes, including NQO1, GCLC , and GCLM (glutamate cysteine ligase, modulatory subunit) (58). The latter genes improve redox balance, as reflected in a higher ratio of reduced to oxidized glutathione (GSH/GSSG, GSH being the most abundant intracellular antioxidant), and this additional protection against ROS confers a survival advantage to the tumor cells (58).…”
Section: Thyroid Carcinomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, when TROP-2 were combined to CD56, the sensitivity and NPV increased to 100% and had a better diagnostic accuracy, further supporting the interest for CD56 [20]. Again, NRG1 was also recently reported to be highly expressed in PTC compared with adjacent normal tissues [21].…”
Section: Immunohistochemical Markersmentioning
confidence: 69%
“…To deeply investigate the mechanism by which CASC9 exerted its tumorigenesis role in HAs, the target of miR-125a-3p was also predicted. NRG1 was confirmed as a target of miR-125a-3p, which is recognized as an oncogene in gastric cancer,19 colon cancer,20 lung cancer,21 and papillary thyroid cancer 22. Yin et al23 reported that miR-125a-3p affected cell apoptosis and invasion through regulating Nrg1 in human glioma cells.…”
Section: Discussionmentioning
confidence: 99%